Genetic diversity and population structure of Kudouzi (Sophora alopecuroides) in Northwest China revealed by SNP markers and seed phenotypic traits - Luo, Cunkai; Ma, Fanyan; Niu, Panxin; Zhang, Zhao; Chen, Weiting; Jiang, Ping; Wang, Mei; Chu, Guangming; Huang, Xiang (Frontiers in Plant Science, 2025)
IntroductionSophora alopecuroides L., a perennial leguminous herb native to northwest China, holds medicinal, ecological, and forage value. However, intensified human activities have caused a sharp decline in its wild populations and genetic diversity.MethodsTo assess its genetic structure and diversity, we analyzed 65 wild populations using SNP markers and seed phenotypic traits.ResultsThe coefficient of variation for eight seed traits ranged from 2.87% to 7.94%, with diversity indices (H) from 1.639 to 1.767, indicating rich phenotypic variation. Clustering based on phenotypic traits and SNP data both divided populations into two main groups. Genetic diversity was relatively low (He = 0.22; Ho = 0.17; Pi = 0.19), and AMOVA showed that variation was mainly among individuals (132.83%), with low population differentiation (FST = 0.00-0.04). Redundancy analysis revealed that phenotypic traits were largely influenced by mean temperature of the driest quarter and annual wind speed, while genetic diversity was shaped by precipitation and thermal variables.ConclusionsOur results provide a foundation for understanding the genetic variation of S. alopecuroides, offering valuable insights for its conservation and breeding programs.